Mobile Application for English Reading Comprehension - S Agustini; N P Wardhani; M Kurniawan; E N Amalina (IPTEK Journal of Proceedings Series, 2018)
Test of Teaching English of Foreign Language or TEFL is one of the scourges for students who must take this test for their graduation term. Many of them got a lack of motivation to learn, especially engineering students. Reading comprehension is one of the tests in TEFL test. However, many students failed in this section because they did not understand the text well and they had less of vocabulary. The students needed a mobile application which able to bring everywhere and they could learn the material and do the exercise anytime. Mobile application based on Android platform is the answer to help the students. In this application the students would learn the material of reading comprehension and do the exercise which divided into 3 levels; from the easier to the hardest.